Pengaruh Intervensi Spiritual Terhadap Kesejahteraan Psikologis Pada Kanker Ginekologi Di RSUD Prof. Dr. Margono Soekarjo Purwokerto - Aniarti, Reni (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: To examine the effect of spiritual intervention on the psychological well-being of gynecological cancer patients at RSUD (Regional Public Hospital) Prof. Dr. Margono Soekarjo Purwokerto. Methods: This quantitative study used a quasi-experimental design with a pre-test and post-test with a control group approach. Samples were taken using consecutive sampling techniques, involving 70 respondents (35 respondents in each group). The researcher directly administered the spiritual intervention. The instrument used to measure psychological well-being was the Ryff's Psychological Well-Being Scale (PWBS). Data were analyzed using the Wilcoxon Signed Ranks and Mann-Whitney U tests. Results: There was a positive difference in psychological well-being between the intervention group and the control group after the intervention (p-value 0.000). Conclusion: Spiritual intervention significantly impacts the psychological well-being of gynecological cancer patients at RSUD Prof. Dr. Margono Soekarjo Purwokerto. Keywords: spiritual intervention, psychological well-being, gynecological cancer